Esensi dan Eksistensi Putusan Pengadilan Perilaku Hakim Menerima Suap: Kajian Teori Dekonstruksi Derrida Kritik Prosedural: The Essence and Existence of Court Decisions: Judges' Behavior in Accepting Bribes: A Study of Derrida's Deconstruction Theory, Procedural Criticism - Putu Ayu Veguita Putri Ningsih; Abdul Rahman (Jurnal Hukum Pidana Indonesia, 2024)
Judges are symbols of integrity, neutrality, and objectivity in the courts. However, when a judge accepts a bribe, the act can undermine the principles of value as a judge, and the bribe has the potential to influence legal decisions that should be based on evidence, facts, and authoritative/juridical texts. The impact of judges accepting bribes is detrimental to the judicial system, as bribery can certainly harm public trust in the judicial system and compromise the integrity of the judiciary. The purpose of the research is to analyze the form of justice to the aggrieved party of the court decision due to bribery to the panel of judges based on Derrida's Deconstruction theory. The research method used is normative juridical, an approach by studying the provisions and rules in the form of legal rules or legal provisions along with existing legal principles. The phenomenon of judges accepting bribes, the need for firm and effective anti-corruption decision-making, the establishment of an independent supervisory system, the imposition of strict sanctions on judges proven to accept bribes, and increasing the integrity of judges through ethics training and character assessment, stopping the culture of bribery in judges is an important step towards a fair and transparent judiciary. Society needs to work together to eradicate corruption in the justice system for the sake of justice.